Ewolucja ewolucjonizmu z popperowskiego punktu widzenia - Jodkowski, Kazimierz (Filozofia Nauki, 2003)
In this paper, I analyse the transition from gradualism to punctualism. I try to respond to the following question: Is the transition in question connected with an increase or decrease of falsifiability? My answer to that question is that from the classical Popperian point of view theory of Punctuated Equilibria is a failure because it does not satisfy the Popperian criteria of progress in the development of science. Classical Darwinism and Neodarwinism have failed in that they predict a number of transitional forms in the fossil record that have never been found. The Punctuated Equilibria theory predicts abrupt appearance of new species and a following stasis. But it is hardly any success, as far as explanatory power is concerned, because the theory in question does not predict really any new facts, it may, therefore, be viewed as an ad hoc proposal. Moreover, its claims are, I argue, unfalsifiable to all practical ends and purposes.